2002
DOI: 10.1002/chin.200217132
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Synthesis and SAR of Aziridinylquinoline‐5,8‐diones as Agents Against Malignant Tumor Cells.

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 100 leading journals. To access a ChemInform Abstract of an article which was published elsewhere, please select a “Full Text” option. The original article is trackable via the “References” option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Connection of 5,8-quinolinedione with a 2-methylaziridinyl fragment led to compounds 55 – 57 and 58 – 60 (Figure 9), which exhibited a moderate activity depending on the R group. The research showed that the substituent type affects cytotoxic activity as follows: amine ( 57 and 60 ) > methoxy ( 56 and 59 ) > chloride ( 55 and 58 ) [72].…”
Section: Biological Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Connection of 5,8-quinolinedione with a 2-methylaziridinyl fragment led to compounds 55 – 57 and 58 – 60 (Figure 9), which exhibited a moderate activity depending on the R group. The research showed that the substituent type affects cytotoxic activity as follows: amine ( 57 and 60 ) > methoxy ( 56 and 59 ) > chloride ( 55 and 58 ) [72].…”
Section: Biological Activitymentioning
confidence: 99%
“…A comparison of activities in both series of compounds showed that the derivatives containing the aziridinyl moiety at the C-6 position ( 58 – 60 ) were characterized by a higher cytotoxicity against the SK-OV-3, SK-MEL-2, and XF498 cell lines than the C-7 analogues 55 – 57 [72].…”
Section: Biological Activitymentioning
confidence: 99%